Chaotic satellite synchronization using neural and nonlinear controllers. (April 2017) - Farzami Sarcheshmeh, Saeed; Esmaelzadeh, Reza; Afshari, Mehdi
Highlights: In this paper, two chaotic satellites are modeled. Two neural controllers (NARMA-L2 and Predictive) and a Nonlinear controller are designed to synchronize two chaotic satellites. The simulation results have been compared with another control method (Active control). Both of the neural controllers do a bounded error tracking and the Nonlinear and Active controllers do a perfect tracking. The Nonlinear controller has the best performance (so low amounts of produced control signals and the highest accuracy and speed of the synchronization). Abstract: In this paper, two master and slave chaotic satellites will be synchronized acceptably using two different control methods. The first method is based on the neural networks in which two neural controllers called NARMA-L2 and Predictive controllers will be designed. In the second method a Nonlinear controller is designed by the Feedback linearization approach. The simulation results of the designed controllers have been compared with a performed control method called Active control to verify the effectiveness of the proposed controllers and to show the advantages and disadvantages of each one.